Potamalpheops yamakawai n. sp., representing the first record of the genus from Japan (Decapoda: Caridea: Alpheidae) - Yamashita, Ryunosuke; Komai, Tomoyuki; Koreeda, Reo (Zootaxa, 2024)
In the present study, a new species of the alpheid shrimp genus Potamalpheops Powell, 1979, Potamalpheops yamakawai, is described from Japan. The new species, representing the first species of the genus to be recorded from the Japanese waters, appears to be close to P. miyai Yeo & Ng, 1997, known from mangroves in Indonesia and the Philippines, among the 16 previously known congeners. The non-setose ventrolateral margin of the carapace, the lack of spiniform setae on the pereopod 5 merus, the simple posterolateral tooth of the uropodal exopod and the overall colouration distinguish P. yamakawai sp. nov. from P. miyai. Genetic analysis using the mitochondrial 16S rRNA gene suggests that the new taxon is not conspecific with P. miyai. Specimens of the new species were collected from upstream of tidal limit to estuarine habitats, sometimes inhabiting burrows of other animals.